Penggunaan Alat Penggerek Metal dan Herbisida Glifosat untuk Pengendalian Gulma Bambu Tabah (Gigantochloa nigrociliata Kurz.) di Perkebunan Kelapa Sawit - Toto Suryanto (JURNAL CITRA WIDYA EDUKASI, 2018)
Bamboo is a dominant weed in palm oil plantations are generally controlled by pruning, but the type of control is less effective for weed regrowth of tall bamboo. Giving a systemic herbicide Glyphosate through the drilling process using a metal borer on a bamboo is a alternative weed control can be performed. Weed drilling method is effective in controlling weeds because the active ingredients will directly attack the carrier networks that exist on the stem of the weed. The experimental design used is non factorial completely randomized design with three replications. The treatments tested were giving various doses of Glyphosate, which is 10 ml, 20 ml, 30 ml, 40 ml and 50 ml. The results showed that the tool metal borer and herbicide Glyphosate can be an alternative weed control resilient bamboo in palm oil plantations. The use of metal borer and herbicide Glyphosate significantly affect physical changes weed stems and leaves of resilient bamboo. Glyphosate herbicide dose that is right for weed control resilient bamboo is 50 ml, but not significantly different with a dose of 40 ml.